Pengaruh Disiplin Kerja, Kompensasi, dan Lingkungan Kerja Fisik terhadap Produktivitas Kerja pada PT Anugrah Jaya Drajat (Jurnal Simki Economic, 2024)
This study aims to analyze and examine the influence of work discipline, compensation, and physical work environment on employee productivity at PT Anugrah Jaya Drajat. The research method used is a quantitative approach, involving 73 employees as respondents. Data analysis uses descriptive statistical techniques and regression analysis. The data analysis technique in this study uses the Partial Least Square (PLS) analysis method with the help of the SmartPLS version 4.0 application. The research results show that work discipline and compensation have a positive and significant effect on employee productivity. However, the physical work environment does not affect productivity at PT Anugrah Jaya Drajat. This indicates that to increase employee productivity, the company needs to pay attention to aspects of work discipline and compensation provided. Meanwhile, the physical work environment is not a dominant factor influencing employee productivity in this company.